Adenovirus gene transfer causes inflammation in the brain. - Byrnes, A; Rusby, J; Wood, M; Charlton, H (1995)
We report that injecting an E1-deleted, non-replicating, human adenovirus type 5 vector into the brain leads to an inflammatory response. Much of this inflammation is induced directly by the virion particles themselves rather than through the expression of new proteins from the vector. The severity of inflammation was found to depend on the strain of inbred rat used: PVG rats have less inflammation than AO rats in response to a vector injection. Twelve hours after injection of adenovirus vectors into the striatum of AO rats, leukocytes were seen marginating to the walls of nearby blood vessels. By two days there was a large increase in major histocompatibility complex class I expression and a heavy infiltration of leukocytes, mainly macrophages and T cells. Retrograde transport of adenovirus to neurons of the substantia nigra was associated with a delayed and less intense inflammation at this distant site. Although AO and PVG rats showed comparable responses in the striatum up to six days, at later times PVG rats had less intense inflammation. In spite of the inflammatory response, vector-driven expression of the marker protein beta-galactosidase and an adenovirus early protein was seen for at least two months following the injection, although expression declined with time. The observation that adenovirus gene transfer leads to an inflammatory response in the brain must be taken into account when planning and interpreting experiments with these vectors. Furthermore, we conclude that using an appropriate strain of rat can diminish some aspects of the inflammation.